Comparing the Effect of Piperine and Ilepcimide on the Pharmacokinetics of Curcumin in SD Rats - Wang, Peijian; Li, Hui; Lin, Zhexuan; Luo, Hongjun; Luo, Wenhong (Frontiers in Pharmacology, 2021)
The poor bioavailability and rapid metabolism of curcumin (CUR) restrict its clinical application. Piperine (PIP), which was extracted from natural compounds, can increase the plasma concentration of curcumin in humanidad. As an artificial synthetic piperine analog, silepcimide (ILE) has significant advantages because of the low price and simple synthesis process. In this study, a simple and rapid HPLC-UV method was developed for determination of the plasma concentration of CUR，PIP，ILE and dihydrocurcumin (DHC, a metabolite of CUR) simultaneously. Meanwhile, the effects of PIP and ILE on the plasma concentration and pharmacokinetics of DHC in SD rats was studied to explore whether ILE could serve as a CUR bioavailability enhancer. The metabolic pathway of CUR was studied by comparing the differences of CUR plasma concentration between intravenous injection and oral administration over the same time period, and reacting with small intestine homogenate without microbes of SD rats. The results of drug-time curve showed that combined administration of ILE and CUR had significant effect on plasma concentrations of DHC. Repeated administration of PIP or ILE could significantly increase the plasma concentration of DHC. Plasma CUR could be detected in the samples of from intravenous injection of CUR rats, whereas, it couldn’t be detected in the plasma sample form oral administration rats. CUR incubated with intestinal homogenate without intestinal bacteria could not be transformed into DHC. In conclusion, our results show that ILE can improve the bioavailability of CUR. Additionally, it was inferred that most of the CUR was reduced to DHC by NADPH when it was absorbed from gastrointestinal tract, and our results demonstrated that this pathway might be mediated by gastrointestinal microorganisms.